Barriers to adherence to endotracheal tube suctioning guidelines among intensive care nurses at a Tanzanian national hospital: A qualitative study - Loema Moshi Buyi; Rashid Heri; Menti Lastone Ndile (PLoS ONE, 2026)
Background Endotracheal tube suctioning (ETS) is a critical procedure for mechanically ventilated patients. Evidence-based guidelines exist to ensure its safe performance; however, adherence remains suboptimal, especially in resource-limited settings. This study aimed to explore the barriers to ETS guideline adherence among ICU nurses at Muhimbili National Hospital (MNH), Tanzania. Methods An exploratory qualitative study was conducted in the medical and surgical ICUs of MNH. Seventeen ICU nurses with ≥1 year of experience were purposively sampled. Semi-structured interviews were performed, audio-recorded, transcribed verbatim, and analyzed using inductive thematic analysis following Braun and Clarke’s framework. Results Three key barriers emerged: (1) Resource scarcity, including critical shortages of staff, equipment, and supplies; (2) Human and behavioral challenges, such as knowledge deficits and resistance to change away from routine practice; and (3) Guideline accessibility and usability, concerning poor accessibility and a perception that guidelines were not tailored to the local context. Conclusion Non-adherence to ETS guidelines primarily reflects systemic constraints rather than individual neglect. Strengthening adherence requires multi-level interventions: improving staffing and resources, providing continuous training, and adapting international guidelines to the local context.